Chikungunya patient transcriptional signatures faithfully recapitulated in a C57BL/6J mouse model - Bishop, Cameron R.; Caten, Felipe Ten; Nakaya, Helder I.; Suhrbier, Andreas (Frontiers in Immunology, 2022)
An adult wild-type C57BL/6J mouse model of chikungunya virus (CHIKV) infection and disease has been extensively used to study the alphaviral arthritic immunopathology and to evaluate new interventions. How well mouse models recapitulate the gene expression profiles seen in humans remain controversial. Herein we compare RNA-Seq datasets from the C57BL/6J CHIKV mouse model with datasets obtained from adults and children acutely infected with CHIKV. Despite sampling quite different tissues, peripheral blood from humans and feet from mice, gene expression profiles were quite similar, with an overlap of up to ≈50% for up-regulated single copy orthologue differentially expressed genes. Furthermore, high levels of significant concordance between mouse and human were seen for immune pathways and signatures, which were dominated by interferons, T cells and monocyte/macrophages. Importantly, predicted responses to a series of anti-inflammatory drug and biologic treatments also showed cogent similarities between species. This mouse model thus provides a reliable and representative system in which to study CHIKV immunopathology and evaluate new treatments.